Effect of Morus alba on the flavonoids content and bromatological profile of goat milk - García-Valádez, Julio César; Carmona-Hernández, Oscar; Bulbarela-Sampieri, Carmen; López-Del-Castillo-Lozano, Micloth; Aguirre-Martínez, Ana María; Lozada-García, José Armando (Agronomía Mesoamericana, 2021)
Introduction. Mulberry (Morus alba), a plant native to China, is used as a fodder on some farms. Its high protein content stimulates milk production in cattle; however, it is not known whether its flavonoids can be incorporated into goat milk. Objective. To evaluate the effect of a diet enriched with mulberry-enriched, on flavonoids concentration and bromatological parameters of milk from stabled alpine goats. Materials and methods. The experiment was carried out in 2019, with goats from a particular farm located in Veracruz, Mexico. Two groups were formed (A with the treatment and B control) with five Alpine breed goats each, with similar characteristics (stall feeding, three calving, without mastitis, morning and evening hand milking). Group A received forage without mulberry before and after treatment (days 1-10 and 21-31, respectively), and a modified forage diet with mulberry (days 11-20; group B was fed forage without mulberry on all 31 days of experimentation. Additionally, the flavonoid content in mulberry and every three days in milk samples were analyzed, in addition to the bromatological content of protein, fat, lactose, non-fat solids, and density. Results. During the mulberry-modified diet, the flavonoid concentration reached a maximum of 53.45 mg mL-1 EQ in group A at day 20, it decreased gradually during the post-treatment period; however, it maintained 20 % more flavonoids than the control group. A significant increase in protein content was also observed in group A, with no significant difference in the other bromatological parameters of the milk between the two groups. Conclusions. The diets modified with mulberry favored the incorporation of flavonoids and the increase of protein in goat milk, without modifying the other bromatological parameters.